Health nursing in the care of children: perspectives of the community nursing practice (Revista Latino-Americana de Enfermagem, 2000)
The study aims at analysing the community health nursing practice in the care of children and to point out the perspectives for the coming millenium. The study was conducted by review of the literature. It provides a brief synthesis of the current social context and a short historic reflection about health practices with children and community health nursing practice. It is observed that the practice of nursing is conducted according to the official Health Assistance Program for Children. Despite its goals, however, the program has not been efficient. In this way it will be valued the multiprofessional work in the accompaniment of the growth and developement, domiciliary visit, and "groups of mothers" in which the nurse will be a coparticipant of the staff, with the great contribuition that health professionals with preventions and promotions background frequently offer.